Crystal structure of 4-allyl-5-pyridin-4-yl-2,4-dihydro-3H-1,2,4-triazole-3-thione, C10H10N4S - Öztürk Yildirim, Sema; Akkurt, Mehmet; Çetin, Ahmet; Cansiz, Ahmet; Şekerci, Memet; Heinemann, Frank W. (Japan Society for Analytical Chemistry, 2005)
The crystal structure of C10H10N4S, was determined by X-ray diffraction at low temperature (100 K). The compound crystallizes in monoclinic P21/c; a = 8.006(5)Å, b = 15.363(5)Å, c = 8.936(5)Å, ? = 104.441(5)°. The molecular structure is non-planar. The crystal packing is stabilized by N-H·N and C-H·S type hydrogen bonds. 2005 © The Japan Society for Analytical Chemistry.